A novel gene SpCTP3 from the hyperaccumulator Sedum plumbizincicola redistributes cadmium and increases its accumulation in transgenic Populus × canescens - Li, Shaocui; Zhuo, Renying; Yu, Miao; Lin, Xiaoyu; Xu, Jing; Qiu, Wenmin; Li, Haiying; Han, Xiaojiao (Frontiers in Plant Science, 2023)
A cadmium (Cd) tolerance protein (SpCTP3) involved in the Sedum plumbizincicola response to Cd stress was identified. However, the mechanism underlying the Cd detoxification and accumulation mediated by SpCTP3 in plants remains unclear. We compared wild-type (WT) and SpCTP3-overexpressing transgenic poplars in terms of Cd accumulation, physiological indices, and the expression profiles of transporter genes following with 100 μmol/L CdCl2. Compared with the WT, significantly more Cd accumulated in the above-ground and below-ground parts of the SpCTP3-overexpressing lines after 100 μmol/L CdCl2 treatment. The Cd flow rate was significantly higher in the transgenic roots than in the WT roots. The overexpression of SpCTP3 resulted in the subcellular redistribution of Cd, with decreased and increased Cd proportions in the cell wall and the soluble fraction, respectively, in the roots and leaves. Additionally, the accumulation of Cd increased the reactive oxygen species (ROS) content. The activities of three antioxidant enzymes (peroxidase, catalase, and superoxide dismutase) increased significantly in response to Cd stress. The observed increase in the titratable acid content in the cytoplasm might lead to the enhanced chelation of Cd. The genes encoding several transporters related to Cd2+ transport and detoxification were expressed at higher levels in the transgenic poplars than in the WT plants. Our results suggest that overexpressing SpCTP3 in transgenic poplar plants promotes Cd accumulation, modulates Cd distribution and ROS homeostasis, and decreases Cd toxicity via organic acids. In conclusion, genetically modifying plants to overexpress SpCTP3 may be a viable strategy for improving the phytoremediation of Cd-polluted soil.